P-Nitrophenyl acetate hydrolysis promoted by Zn(II) and Co(II) complexes with the tripodal ligand of N, N′-bis(2-quinolinylmethyl)amantadine. Issue 1 (2nd January 2017) - Zhou, Ying-Hua; Liu, Xian-Wen; Tao, Jun; Wang, Su-Qin; Ren, Ping; Ni, Ping; Cheng, Yong
Abstract: To mimic the function of metallohydrolase, [M(bqad)Cl2 ] (M = Zn(II) (1 ), Co(II) (2 ), where bqad =  N, N ′-bis(2-quinolinylmethyl)amantadine), have been synthesized and characterized by elemental analysis, electronic absorption, IR, and single crystal X-ray diffraction. The structural analysis indicated that metal ions in1 and2 were coordinated by three nitrogens from bqad and two chlorides, resulting in a distorted trigonal bipyramidal geometry. Kinetic experiments for hydrolytic cleavage of p -nitrophenyl acetate ( p NA) catalyzed by1 and2 were performed at pH 7.50–10.00 and 298 K. The second-order rate constants ( k obs ) increased exponentially with variation of pH values. The Co(II) complex exhibited potent catalytic activity. Abstract :